Faktor dan pola pengasuhan pada pasangan remaja di Kecamatan Ngantang: Studi kasus adolescent parenting: Parenting factors and patterns in adolescent couples in Ngantang sub-district: A case study of adolescent parenting - Niara Urvira Muliyati; Farah Farida Tantiani (LP2M Universitas Sarjanawiyata Tamansiswa, 2024)
Adolescent parenting is child care carried out by parents who are still teenagers. Ngantang District is one of the areas with the highest number of early marriages, reaching 20%-30% of teenagers. Therefore, this research aims to determine the factors that make teenage couples marry and have children at an early age and how parenting patterns or implementation of adolescent parenting in teenage couples are in accordance with Bigner & Gerhald's adolescent parenting theory. This research uses a qualitative approach with a case study type of research that focuses on exploring bound systems. The subjects in this research were determined using a purposive sampling technique and checking the validity of the data was carried out using the source triangulation method. The research results illustrate the role of parental support in the motivation of teenage couples and out-of-wedlock pregnancies to have children at an early age. The pattern of adolescent parenting in this study shows that adolescent couples provide quite good responsiveness to children but are less demanding, so it can be categorized as permissive parenting. It was also found that there were differences between adolescent parenting by adolescent fathers and mothers, lack of education and knowledge influenced the pattern of adolescent parenting provided.